1991
DOI: 10.1021/bi00219a015
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold-attached regions from the human interferon .beta. domain can be used to enhance the stable expression of genes under the control of various promoters

Abstract: We have transfected DNA corresponding to the complete chromatin domain of human interferon beta (huIFN-beta) gene into mouse L cells. In this construct, which is flanked by scaffold-attached regions (SARs), the gene's transcription was enhanced 20-30-fold with respect to DNAs containing only the immediate regulatory elements. To elucidate the role of SAR elements in the transcriptional enhancement, their position was varied relative to several artificial promoter-gene combinations. It was found that SARs enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
138
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(145 citation statements)
references
References 35 publications
6
138
0
Order By: Relevance
“…A transgene flanked by S/MAR elements may therefore constitute an autonomous chromatin domain whose expression would remain independent of the adjacent chromosomal environment. Consistent with this view, S/ MARs have been shown to increase the expression of adjacent transgenes when co-inserted into a chromosomal environment (Kalos and Fournier, 1995;Klehr et al, 1991;Phi-Van et al, 1990;Poljak et al, 1994). …”
Section: Introductionmentioning
confidence: 67%
“…A transgene flanked by S/MAR elements may therefore constitute an autonomous chromatin domain whose expression would remain independent of the adjacent chromosomal environment. Consistent with this view, S/ MARs have been shown to increase the expression of adjacent transgenes when co-inserted into a chromosomal environment (Kalos and Fournier, 1995;Klehr et al, 1991;Phi-Van et al, 1990;Poljak et al, 1994). …”
Section: Introductionmentioning
confidence: 67%
“…These elements control gene expression by supposedly altering the chromosomal structure. Assessment of their regulatory function is therefore dependent upon the nucleosomal organization of the DNA (Klehr et al, 1991) and remains undetected in transient assays where naked DNA is examined. Madisen and Groudine (1994) showed that elements other than the Ca-enhancer were also necessary for c-myc deregulation in a murine mouse plasmacytoma.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix attachment regions (MARS), containing extensive runs of AT residues, have been shown to confer position and orientation independence to transcriptional properties of several genes in vitro and in vivo [Stief et al, 1989;Phi-Van and Stratling, 1990;Gasser et al, 1989;von Kries et al, 1991;Luderus et al, 1992;Klehr et al, 1991;Bonifer et al, 19901. These stable gene attachment sites mediate long-range influences covering several hundred kb [Jarman and Higgs, 19881.…”
Section: Introductionmentioning
confidence: 99%